Rapid Residue Analysis of Phthalanilic Acid in Cereals and Oilseed Rape by High-Performance Liquid Chromatography Coupled to Tandem Mass Spectrometry - Aijuan Zhang; Li Zhou; Miao Yu; Yizhi Feng; Yanli Bian; Jinju Pan; Bojun Zuo; Lin Liang (Journal of Chemistry)
Phthalanilic acid is widely used in wheat and oilseed rape fields in China, but there is no analysis method to detect its residues in wheat and oilseed rape substrates. To accurately evaluate the health and environmental impact of phthalanilic acid residues on wheat gains and rapeseeds, it is urgent to establish a reliable analytical method for its detection. In this study, a rapid and sensitive method was developed based on QuEChERS and LC-MS/MS to detect phthalanilic acid in cereals (wheat, rice, corn, and millet), wheat straw, and rapeseeds. Optimization of the detection conditions showed that the mobile phase of acetonitrile-0.1% formic acid solution had the best chromatographic resolution and sensitivity. The average recovery rates of phthalanilic acid in cereals, wheat straw, and rapeseeds ranged from 88% to 113% with relative standard deviations (RSDs) of 1%–6%. There were good linear relationships with the correlation coefficients (r) higher than 0.9990 at concentrations of 0.01–5 mg L−1. The limits of quantification (LOQ) for phthalanilic acid in cereals, wheat straw, and rapeseeds were 0.01 mg kg−1, 0.05 mg kg−1, and 0.02 mg kg−1, respectively. These results show that the method established in this study is convenient and reliable for routine monitoring of phthalanilic acid in cereals, wheat straw, and rapeseeds.